2022
DOI: 10.1371/journal.pone.0263921
|View full text |Cite
|
Sign up to set email alerts
|

Final HIV status outcome for HIV-exposed infants at 18 months of age in nine states and the Federal Capital Territory, Nigeria

Abstract: Introduction While antiretroviral therapy (ART) coverage for pregnant women has undergone steady scale-up, Nigeria’s final mother- to-child transmission of HIV (MTCT) rate remains unacceptably high at 10%. This study aimed to determine final outcomes (MTCT rates) and their correlates among HIV-exposed infants (HEI) in nine states and the Federal Capital Territory, Nigeria. Methods This retrospective, cross-sectional study was conducted at 96 primary, secondary and tertiary health facilities supported by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…A report from Nigeria revealed an incidence of HIV infection among HIV exposed infants to be 2.8% which is nearer to the WHO indicator of below 2% and this study reported the Lost to Follow Up(LTFU) rate of 7.3% (LTFU) and rural maternal residence, lack of maternal ART/ARV prophylaxis, mixed infant feeding and infant birth weight less than 2.5 kg were found to have correlation with risk of HIV-infection in HIV exposed infants ( 4 ). A study done in 5 Amhara regional state, Ethiopia, referral Hospitals to assess attrition rate (Death, Lost to follow up) of HIV exposed infants reported that the cumulative incidence of LTFU was 19 (8.8%), (95% CI, 5.4%-12.4%) among 217 exposed infants enrolled to the PMTCT department between January 2014 and 2017 and the cumulative incidence of mortality in the region was zero ( 5 ).…”
Section: Introductionmentioning
confidence: 76%
“…A report from Nigeria revealed an incidence of HIV infection among HIV exposed infants to be 2.8% which is nearer to the WHO indicator of below 2% and this study reported the Lost to Follow Up(LTFU) rate of 7.3% (LTFU) and rural maternal residence, lack of maternal ART/ARV prophylaxis, mixed infant feeding and infant birth weight less than 2.5 kg were found to have correlation with risk of HIV-infection in HIV exposed infants ( 4 ). A study done in 5 Amhara regional state, Ethiopia, referral Hospitals to assess attrition rate (Death, Lost to follow up) of HIV exposed infants reported that the cumulative incidence of LTFU was 19 (8.8%), (95% CI, 5.4%-12.4%) among 217 exposed infants enrolled to the PMTCT department between January 2014 and 2017 and the cumulative incidence of mortality in the region was zero ( 5 ).…”
Section: Introductionmentioning
confidence: 76%